Pattern of skin disease in Ethiopian HIV‐infected patients on combination antiretroviral therapy: A cross‐sectional study in a dermatology referral hospital - F. Shikur; H. Yeung; W. Amogne; R. Weller (Wiley, 2021)
Abstract Background More than 90% of human immunodeficiency virus (HIV)‐infected patients will develop at least one type of skin disorder during the course of the disease. The prevalence and severity of skin disease commonly seen in HIV‐infected patients has decreased in the era of combination antiretroviral therapy (cART). Few studies in Ethiopia have shown the magnitude of skin problems among adult patients on cART. The aim of this study is to describe the pattern of skin disease among adult patients who are on cART. Methods Cross‐sectional observational study at ALERT Hospital from April 2018 to November 2018. Patterns of clinically diagnosed skin diseases were summarized descriptively. Result A total of 572 patients were evaluated. In total, 412 (72%) were female and the mean age of study participants was 40 (SD = 10.4). The median CD4 count at the time of diagnosis and start of cART were 178 (R 5‐2000) and 168 cells/μl (R 5‐1327), respectively. The mean duration of cART was 8 (SD = 3) years. 89.3% of patients were on first line and 7% on second line of cART regimen. Noninfectious inflammatory skin disorders (40.9%) were the most common concomitant diagnosis followed by infectious diseases (34.9%), infestation (7.7%), pigmentary disorders (6.3%) and cutaneous drug eruption (0.7%), respectively. Among the inflammatory skin disorders, 56.5% presented with eczema. One patient had Kaposi sarcoma. Conclusion Noninfectious inflammatory skin disorders are the most common concomitant skin disease in HIV‐infected patients, with eczema being most prevalent. Infectious skin diseases were also common presentations. In our study, AIDS‐defining skin conditions were rare.